Extension of Time In Construction Projects - A.K. Mishra; Madan Sharma; Janani Selvam (MEC-J (Management and Economics Journal), 2022)
Timely complementation of project is highly focused. With an aim to assess the consequences of time extension in terms of project’s performance i.e time and cost based on cases of Nepal. The questionnaire contained statements on practices adopted of Eot in construction field, consequences of Eot in the project’s cost and time and impacts of Eot in the project’s performance through literature review. Also, the impacts of Eot in the project’s performance were tested through Hypothesis test method. Total of four statements from practices adopted in construction, seventeen statements from the consequences of Eot and Four statements from the impacts of Eot in projects performance were established and administrated on twelve projects for collecting the information. The identified results were analyzed with Relative Importance Index (RII) and Ranking. The significant impacts of cost, time and quality were tested on project performance by Regression as set Hypothesis.  Overall RII of practices adopted of Eot in construction field as timing of Eot claim varied from maximum 0.813 to minimum 0.74. The RII of consequences of Eot varied from maximum 0.920 to minimum 0.600. Architect too busy with other tasks attend the bottom position based on overall RII rank value.